Efficacy of quinolones and cephalosporins against antibiogram of Escherichia coli isolated from chickens - Lakho, Ranjhan Ali; Abro, Shahid Hussain; Tunio, Muhammad Tarique; Zubair, Mohsina; Abro, Rani; Rind, Rahmatullah; Leghari, Riaz Ahmed; Malhi, Kanwar Kumar; Rind, Muhammad Rafique; Kamboh, Asghar Ali (Journal of Pure and Applied Agriculture, 2023)
Colibacillosis is an acute septicemia disease caused by E. coli producing considerable morbidity and mortality especially in poultry. Quinolones and cephalosporins have been used in treatment of various infections. Therefore, this study was designed to evaluate the efficacy of quinolones and cephalosporins against the antibiogram of E. coli isolated from chicken flocks. The 100 blood samples from liver and intestine were collected from different poultry vendors surrounding of Tandojam and Hyderabad, Sindh, Pakistan. The isolated organism was cultured on nutrient and blood agar media. The cultural, morphological and biochemical characteristics were observed for the confirmation of the isolated organism. The minimum inhibitory concentration (MIC) of different antibiotics against E. coli was performed by serially diluting antibiotics ciprofloxacin, metronidazole, cefipime as 0.4 µg/ml, 0.8 µg/ml, 1.6 µg/ml, 3.2 µg/ml and 6.4 µg/ml, 12.5 µg/ml, 25 µg/ml and 50 µg/ml, respectively. The mean zones of inhibition of ciprofloxacin, ofloxacin, enrofloxacin, norfloxacin, cefepime, ceftazidimine and cefoxitin against the antibiogram of E. coli were recorded as 14, 11, 12, 11, 11, 11, and 11 mm, respectively. MIC results indicated that ciprofloxacin was found to be more effective to inhibit the growth of E. coli. It was found that antibiotics of quinolones group namely ciprofloxacin, enroflaxcin and ofloxacin as well as cephalosporin group namely cefipime, ceftazidime and cefoxitin were found to be effective to isolate E. coli.